Taxonomic review of Sibaria Stål, 1872 (Heteroptera: Pentatomidae: Pentatominae: Carpocorini), with description of a new species - Krein, Verônica; Bianchi, Filipe M.; Rider, David A.; Grazia, Jocelia (Zootaxa, 2020)
Sibaria Stål is a genus of Pentatomidae occurring exclusively in the Neotropical region. Since its description, little information has been added to the knowledge of the taxon. The hypothesis of monophyly of Sibaria was recently supported by a phylogenetic analysis based on morphological and molecular data. The purpose of this study is to provide a review of Sibaria, redescribe the valid species, and describe a new species. The genus includes four species: S. andicola Breddin, S. armata (Dallas), S. englemani Rolston, and S. amazonica sp. nov.. Diagnoses, macrophotographs (habitus, external and internal genitalia), an identification key, and distribution records of the species are also provided.